Ситемно-компонентний аналіз при обліку електронних грошей - Ковальова, Тетяна Володимирівна (НТУ "ХПИ", 2018)
Актуальність цього дослідження полягає у тому, що вченими приділяється недостатньо уваги щодо залучення наукових методів дослідження при вивченні певних об’єктів обліку. У статті обґрунтована можливість використання системно-компонентного аналізу при дослідженні обліку електронних грошей. Цей науковий метод ураховує всі складові (компоненти), які прямо або опосередковано впливають на ефективність облікового процесу електронних грошей. У роботі виділено та досліджено три компонента: "людина", "техніка", "середовище", "процеси".

Actual continuity of this study is that scientists gives insufficient attention to attract scientific research methods in the study of certain objects of accounting. In the article is substantiated the possibility of using system – componential analysis during research of accounting of electronic money. This scientific method takes into account all parts (components) which directly or indirectly affect on efficiency of accounting process of electronic money. In the article was distinguished and researched three components: "man", "technique", "environment", "processes". The proposed correspondence system for accounting for electronic money, is indicated on the peculiarities of conducting analytical accounting. It is proved that system-component analysis helps to increase the efficiency of electronic money use in Ukraine.
System-componential analysis during accounting of electronic money
Keywords: рахунок; система; об’єкт обліку; components; account; system